On the presence of the Late Permian dicynodont Endothiodon in Brazil. (8th February 2013) - Boos, Alessandra D. S.; Schultz, Cesar L.; Vega, Cristina S.; Aumond, Juarês J.
Abstract: The first dicynodont reported for the Permian of South America is described in detail here. The specimen consists of a partial skull and associated lower jaws, collected from the Serra do Cadeado locality, Rio do Rasto Formation, Brazil. The specimen was assigned to the genus Endothiodon Owen in a preliminarily description published in the 1970s. This identification implied a direct correlation with some of the well‐established biozones of the Beaufort Group, South Africa, where this taxon is known to occur. Although badly weathered, the Brazilian material preserves several features that allow us to confirm its assignment to Endothiodon, such as the pineal foramen situated on a boss, the bulbous swellings of the dentaries, a boss situated on the ventral margin of the jugal, the extensive number of dentary teeth and the upturned pointed beak of the lower jaw. However, this set of characters is not enough to establish a specific taxonomic assignment for the specimen, although it seems to be more closely related to E. bathystoma, E. uniseries and E. whaitsi than to E. mahalanobisi . The biostratigraphical correlations proposed for the tetrapod faunas of the Rio do Rasto Formation highlight the similarities between these associations and others from the Mid and Late Permian of South Africa and Eastern Europe. However, until now, these correlations are tentative because only a few faunal elements have been recovered from Brazil, and most of them lack stratigraphic data on the levels from where they were collected. Due to the presence of Endothiodon, at least part of the Rio do Rasto Formation can be correlated with deposits in India, Malawi, Mozambique, South Africa, Tanzania, Zambia and Zimbabwe.